Penerapan Model Problem Based Learning dengan Pendekatan Culturally Responsive Teaching (CRT) untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMP Negeri 31 Medan : Penelitian - Nurhalimah Manurung; Frida Marta Argareta Simorangkir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine whether the application of the Problem Based Learning (PBL) model with the Culturally Responsive Teaching (CRT) approach can improve the mathematical problem-solving abilities of students at SMP Negeri 31 Medan. This study is a classroom action research conducted in two cycles. Each cycle consists of two meetings. The subjects in this study were 28 students of class VIII-3 SMP Negeri 31 Medan. Based on the results of the study, an increase was obtained from cycle I to cycle II. Judging from the average value of the mathematical problem-solving ability test in cycle I, it was 53.22, while the average value of the mathematical problem-solving ability test in cycle II was 78.45. As well as the results of the initial test that had been carried out, 3 students (10.71%) were successful in completing the mathematical problem-solving ability test. In the test cycle I, 11 students (39.28%) succeeded and cycle II, 24 students (85.71%) succeeded in completing the mathematical problem solving ability test. Based on the results of observations that have been carried out, it was obtained that the management of learning carried out by teachers by implementing Problem Based Learning with the Culturally Responsive Teaching (CRT) Approach experienced an increase in cycles with an average of 3.07 (good) to an average of 3.48 (good) in cycle II. In addition, student activities during learning increased where in cycle 1 with an average of 2.33 with a less good category to 3.05 with a good category in cycle II. This proves that the use of Problem Based Learning with the Culturally Responsive Teaching (CRT) Approach can be applied to improve students' mathematical problem solving abilities.